2016
DOI: 10.1038/ajg.2016.96
|View full text |Cite
|
Sign up to set email alerts
|

Access to Subspecialty Care And Survival Among Patients With Liver Disease

Abstract: Access to ambulatory GI care was associated with improved 5-year survival for patients with liver disease. Innovative care coordination techniques may prove beneficial in extending access to care to liver disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 32 publications
6
36
0
Order By: Relevance
“…Patients with a well‐characterized liver diagnosis such as hepatitis B, hepatitis C, cirrhosis, and cirrhosis complications were more likely to have had a SCAN‐ECHO visit. This is consistent with prior patterns seen, in which patients who had these diagnoses were more likely to have a specialty consultation leading to a visit . Similarly, patients with indicators suggestive of more severe liver disease such as elevated ALT and bilirubin were more likely to have had a SCAN‐ECHO visit than no visit.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Patients with a well‐characterized liver diagnosis such as hepatitis B, hepatitis C, cirrhosis, and cirrhosis complications were more likely to have had a SCAN‐ECHO visit. This is consistent with prior patterns seen, in which patients who had these diagnoses were more likely to have a specialty consultation leading to a visit . Similarly, patients with indicators suggestive of more severe liver disease such as elevated ALT and bilirubin were more likely to have had a SCAN‐ECHO visit than no visit.…”
Section: Resultssupporting
confidence: 87%
“…Despite wide uptake of the SCAN‐ECHO program in the VHA, data are limited regarding the clinical impact of VA SCAN‐ECHO, particularly on patient outcomes such as mortality . We previously showed that an in‐person specialist consultation visit is associated with improved survival in liver disease patients . This study sought to extend those findings by examining whether a virtual specialty SCAN‐ECHO consultation visit had a similar positive effect on survival of patients with liver disease.…”
mentioning
confidence: 92%
“…Although APP involvement was associated with higher quality care compared with no APP, the quality of care provided by APPs without gastroenterologists/hepatologists was inferior to that provided by gastroenterologists/hepatologists alone in all categories except 30‐day readmissions. Our findings confirm a prior study from the VA, in which gastroenterology/hepatology consultation was associated with improved outcomes in patients with cirrhosis . However, access to gastroenterologists/hepatologists is limited; among Medicare and VA enrollees, 55% and 67% of patients with cirrhosis, respectively, are never evaluated by a gastroenterologist/hepatologist .…”
Section: Discussionsupporting
confidence: 83%
“…A major barrier to optimal care for cirrhosis is limited access to subspecialty care. Most patients with cirrhosis are not co‐managed by a gastroenterology‐trained or hepatology‐trained specialist . Previous studies have demonstrated that advanced practice providers (APPs) provide care that is equivalent in quality to medical doctors (MDs) in both primary care and specialty care when their practice is focused on one condition .…”
mentioning
confidence: 99%
“…The VA Ann Arbor was one of the first to implement SCAN‐ECHO for chronic liver disease. Having already shown that in‐person specialist consultation visits were associated with improved survival in patients with liver disease, Su et al set out to extend those findings by examining whether a virtual specialty consultation had a similar benefit on survival. Their findings are published in this month’s H epatology …”
mentioning
confidence: 99%